2021
DOI: 10.3389/fonc.2020.599888
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Radiomics Approach Predict Invasiveness of Adamantinomatous Craniopharyngioma Before Surgery

Abstract: PurposeCraniopharyngiomas (CPs) are benign tumors, complete tumor resection is considered to be the optimal treatment. However, although histologically benign, the local invasiveness of CPs commonly contributes to incomplete resection and a poor prognosis. At present, some advocate less aggressive surgery combined with radiotherapy as a more reasonable and effective means of protecting hypothalamus function and preventing recurrence in patients with tight tumor adhesion to the hypothalamus. Hence, if a method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Typically, the surgical outcome is closely associated with the extent of resection (3,7,22). Reports showed that the extent of resection is an independent predictor of tumor recurrence (7,16,17,(23)(24)(25). However, the close association of these tumors with critical neurovascular structures and locally aggressive characteristics make GTR difficult and lead to controversies surrounding the extent of resection in patients with craniopharyngiomas (10,11,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the surgical outcome is closely associated with the extent of resection (3,7,22). Reports showed that the extent of resection is an independent predictor of tumor recurrence (7,16,17,(23)(24)(25). However, the close association of these tumors with critical neurovascular structures and locally aggressive characteristics make GTR difficult and lead to controversies surrounding the extent of resection in patients with craniopharyngiomas (10,11,26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, radiosurgery has been proven to have the potential for better outcomes and decreasing mortality (3,(27)(28)(29). Subtotal resection surgery combined with radiotherapy has been advocated to protect hypothalamus-pituitary function and prevent tumor recurrence (23). In addition, neurosurgical expertise has an important impact on the extent of resection (24,(30)(31)(32), and tumor size may be a predictor of the postoperative functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a nomogram based on independent risk factors can provide more individual and accurate prognosis data for treating clinicians and patients or their relatives. In the last two decades, neurosurgical clinical prediction models have increased exponentially, for a variety of clinical outcomes ( 23 , 45 ). This is the first study to construct models to predict postoperative endocrinological prognosis in patients with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, preoperative evaluation of the tissue invasion of craniopharyngioma is helpful to formulate a more individualized surgical scheme. Ma et al ( 31 ) used a machine learning algorithm combined with radiological characteristics to predict preoperative craniopharyngioma invasiveness. The study cohort consisted of 325 patients in a single institution.…”
Section: The Applications Of Ai In Craniopharyngioma Diagnosismentioning
confidence: 99%
“…Zhang et al ( 28 ) verified five feature selection methods including distance correlation, random forest, Lasso, extreme gradient boosting and gradient boosting decision tree, of which Lasso achieved the best performance. And Ma et al ( 31 ) also adopted Lasso for feature selection. Gutta et al ( 41 ) used the importance score in the gradient boosting algorithm to select the features.…”
Section: Strategies Of Artificial Intelligence In Craniopharyngioma Diagnosismentioning
confidence: 99%